Control Contable de las Cuentas de Ingresos y Gastos del "Comercial Gemelos - Foyain Paguay, Manuel Andrés (2018)
This case study will analyze the ACCOUNTING CONTROL OF THE ACCOUNTS AND EXPENSES OF THE "COMERCIAL GEMELOS" FOYAIN "; it is determined that it is a company that is obliged to keep accounts, but who actually hires an external accountant who only makes the declarations taxes, there is no true accounting control of income and expenses, through the which can determine the result of this business activity. Being obliged to keep accounts and in doing so, the administrator of the business has an instrument for making decisions, by not having this information has caused non-technical decisions, which is not known how it affects the outcome of the operations, it has not been possible to determine with accuracy if this company has had profits or lost. Here we describe that the problem of not keeping an accounting record so The technique of income and expenditure has a series of negative effects on the control of operations carried out by Comercial Gemelos Foyain; among them, that can not be determined accurately the profits or losses, as well as do not have the necessary information to the decision making